Decoding Deconstruction: Unveiling the Layers in Mahakavi Devkota’s Poetic Works - Adhikari, Tara Prasad (The Harvest, 2024)
“Decoding Deconstruction: Unveiling the Layers in Mahakavi Devkota’s Poetic Works” explores the intricate tapestry of Mahakavi Laxmi Prasad Devkota’s poetry, using a deconstructionist point of view. The paper reveals unimagined Deconstructionist features within Devkota’s works, akin to the ideas developed by Jacques Derrida during the 1960s. Devkota has questioned all the so-called hierarchies that were prevalent in Nepali society then. He has questioned human-centric discourses. Thus, his poems exemplify a deconstructive mindset. They invite readers to embrace ambiguity, explore new perspectives and transcend traditional modes of interpretation. This study illuminates how some of the poems by Mahakavi Devkota are so very close to the deconstructionist view developed by Derrida and so e other theorists in the 1970s.